Legal Scholarship Between Metrics and Substance: Preserving the Identity of Slovenian Legal Scholarship in a Globalized Academic Space - Hojnik, Janja (65 pravne znanosti v Mariboru, 2026)
The chapter warns that Slovenian legal scholarship is increasingly adapting to international indexing metrics, threatening its autonomy and distancing research from domestic legal problems. It critically examines the transfer of evaluation methods from the natural sciences into law, which leads to fragmented topics, formalistic publication inflation (accelerated by AI tools), and neglect of issues crucial to the Slovenian legal order. It questions the suitability of bibliometric indicators, especially the journal impact factor, and shows how article assessment is reduced to journal rank. It compares the selective Web of Science – with its biases against non-US, non-English, and specialized law journals - with Finland’s Publication Forum, which relies on peer review rather than citations. It statistically analyses correlations between the two lists and, drawing on a survey of European editors, explains why many leading journals are not in WoS. The chapter argues for content-sensitive criteria tailored to the needs of domestic legal scholarship.